Honduran women in North Carolina. A vision from a gender perspective through five life stories - Rabazo Ortega, Rosa; Vázquez Atochero, Alfonso (Revista Colombiana de Ciencias Sociales, 2025)
This article aims to expose the difficulties faced by people migrating from Latin America to the United States, which are increased in the case of women. Open interviews were conducted with a small group of Honduran women migrants, supporting their arguments through a series of bibliographic documents detailed at the end of the article. This is a work whose originality lies in the fact that the subject of female migration has been little addressed in the social science literature. As a fundamental conclusion, it is worth noting the reproduction at destination of typically female tasks that our informants already carried out at origin, producing a stagnation in their socio-economic conditions of departure. The main limitations found in the course of the research have been related to the location of female interlocutors willing to participate in the study online.